A high-tech, low-cost, Internet of Things surfboard fin for coastal citizen science, outreach, and education. (1st June 2022) - Bresnahan, Philip; Cyronak, Tyler; Brewin, Robert J.W.; Andersson, Andreas; Wirth, Taylor; Martz, Todd; Courtney, Travis; Hui, Nathan; Kastner, Ryan; Stern, Andrew; McGrain, Todd; Reinicke, Danica; et al.
Abstract: Coastal populations and hazards are escalating simultaneously, leading to an increased importance of coastal ocean observations. Many well-established observational techniques are expensive, require complex technical training, and offer little to no public engagement. Smartfin, an oceanographic sensor–equipped surfboard fin and citizen science program, was designed to alleviate these issues. Smartfins are typically used by surfers and paddlers in surf zone and nearshore regions where they can help fill gaps between other observational assets. Smartfin user groups can provide data-rich time-series in confined regions. Smartfin comprises temperature, motion, and wet/dry sensing, GPS location, and cellular data transmission capabilities for the near-real-time monitoring of coastal physics and environmental parameters. Smartfin's temperature sensor has an accuracy of 0.05 °C relative to a calibrated Sea-Bird temperature sensor. Data products for quantifying ocean physics from the motion sensor and additional sensors for water quality monitoring are in development. Over 300 Smartfins have been distributed around the world and have been in use for up to five years. The technology has been proven to be a useful scientific research tool in the coastal ocean—especially for observing spatiotemporal variability, validating remotely sensed data, and characterizing surface water depth profiles when combined with other tools—and the project has yielded promising results in terms of formal and informal education and community engagement in coastal health issues with broad international reach. In this article, we describe the technology, the citizen science project design, and the results in terms of natural and social science analyses. We also discuss progress toward our outreach, education, and scientific goals. Graphical abstract: Image 1 Highlights: Smartfin is an IoT, oceanographic sensor-equipped surfboard fin for citizen science. Over 300 Smartfins have been distributed since 2016. Roughly 2800 h of coastal data have been collected by participants. Smartfin data are useful for coastal physics and remote sensing analyses. Education, outreach, and community are central to project's mission.